2014
DOI: 10.1038/nri3742
|View full text |Cite
|
Sign up to set email alerts
|

Innate sensing of malaria parasites

Abstract: Innate immune receptors have a key role in immune surveillance by sensing microorganisms and initiating protective immune responses. However, the innate immune system is a classic 'double-edged sword' that can overreact to pathogens, which can have deleterious effects and lead to clinical manifestations. Recent studies have unveiled the complexity of innate immune receptors that function as sensors of Plasmodium spp. in the vertebrate host. This Review highlights the cellular and molecular mechanisms by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
320
1
21

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(346 citation statements)
references
References 165 publications
4
320
1
21
Order By: Relevance
“…6 This vectorborne disease causes life-threatening manifestations, particularly in young children, including severe anemia, coma, convulsions, acidosis, and renal failure, among others. 7 In highly endemic regions, malaria in pregnancy (MiP) frequently is asymptomatic but induces maternal anemia, placental inflammation and impaired fetal development, resulting in low birth weight (LBW) and preterm delivery (PD). 8 Lately, the concept of developmental programming of metabolic diseases has been extended to MiP, insofar as it may fuel the upsurge of type 2 diabetes, obesity and hypertension in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…6 This vectorborne disease causes life-threatening manifestations, particularly in young children, including severe anemia, coma, convulsions, acidosis, and renal failure, among others. 7 In highly endemic regions, malaria in pregnancy (MiP) frequently is asymptomatic but induces maternal anemia, placental inflammation and impaired fetal development, resulting in low birth weight (LBW) and preterm delivery (PD). 8 Lately, the concept of developmental programming of metabolic diseases has been extended to MiP, insofar as it may fuel the upsurge of type 2 diabetes, obesity and hypertension in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…The humoral immune response is critical for both acute clearance of blood-stage malaria and protection against subsequent rechallenge (2), yet poor understanding of how to achieve protective humoral immunity hampers vaccine design. The immune response to malaria is initiated when malaria-associated pathogen-associated molecular patterns are recognized by host innate cells via pattern recognition receptors (PRRs) (3). Activation of PRRs has at least two roles in host immunity during blood-stage malaria infection: (a) direct control of parasite replication and/or parasite killing via innate immune effector mechanisms and (b) generation of cues that expand and differentiate antigen-specific CD4 + T cells and B cells (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The immune response to malaria is initiated when malaria-associated pathogen-associated molecular patterns are recognized by host innate cells via pattern recognition receptors (PRRs) (3). Activation of PRRs has at least two roles in host immunity during blood-stage malaria infection: (a) direct control of parasite replication and/or parasite killing via innate immune effector mechanisms and (b) generation of cues that expand and differentiate antigen-specific CD4 + T cells and B cells (3)(4)(5). It was recently reported that the PRR cyclic GMP-AMP synthase (cGAS) was a critical innate signal in the context of a murine model of lethal malaria (6).…”
Section: Introductionmentioning
confidence: 99%
“…Outro dado importante é o desenvolvimento de imunidade natural adquirida em áreas endêmicas, onde indivíduos são infectados diversas vezes pelo parasito. Nestes casos a parasitemia é baixa nestes indivíduos, não ocorrendo à ativação de 15 deletéria de células imune inatas e a infecção é assintomática (GAZZINELLI et al, 2014).Cada espécie de Plasmodium possui suas especificidades, causando manifestações clínicas bastante diferenciadas como observado entre P. vivax e P.falciparaum. Entretanto durante as infecções por causadas por este gênero três principais eventos centrais caracterizam a patogenia da doença: A liberação de citocinas pró-inflamatórias, a adesão de eritrócitos infectados com Plasmodium nos vasos sanguíneos, principalmente cerebrais, bem como a ruptura e remoção destes eritrócitos infectados por macrófagos esplênicos, uma vez que durante o processo infeccioso os mesmos apresentam alterações na membrana plasmática.…”
unclassified
“…Processo este que resulta na polarização de uma resposta Th1 pelas células TCD4+, com produção de IFNγ, ativação de mecanismos efetores da imunidade inata, e principalmente manutenção do pool de células T de memoria contra a infecção por De forma consistente com estes dados, a função de células dendríticas humanas é reduzida quando cultivadas com eritrócitos infectados ou hemozoína (pigmento malárico, um subproduto do metabolismo do Plasmodium) (URBAN et al, 1998). Adicionalmente, foi apresentado que pacientes humanos com malária sintomática por P. falciparum ou P. vivax possuem níveis reduzidos de células dendríticas circulantes, demonstrando que a modulação 21 de células dendríticas é um importante mecanismo de escape do sistema imune desenvolvido pelo parasito (GAZZINELLI et al, 2014). …”
unclassified